Constructing Islamic Ethics through the Prohibition of Arrogance in QS Luqman Verse 18: A Tafsir Maqāṣidī Approach - Siti Rozika; Siti Maryam; Muhyidin Azmi (Lembaga Yasin AlSys, 2026)
Arrogance (takabbur) constitutes a fundamental moral deviation in Islamic ethics that undermines individual spirituality and social harmony. This study aims to interpret the Qur’anic prohibition of arrogance, particularly in Surah Luqman verse 18, through the tafsīr maqāṣidī framework developed by Wasfi ‘Asyur Abu Zayd. Employing qualitative library research, the study drew primary data from the Qur’an and Abu Zayd’s Naḥwa al-Tafsīr al-Maqāṣidī li al-Qur’ān al-Karīm, supplemented by classical and contemporary exegetical literature. The data were analyzed through textual examination, inductive reasoning, maqāṣid formulation, and interpretive verification. The findings reveal that the prohibition of arrogance encompasses linguistic, conceptual, and ethical dimensions, manifested through self-aggrandizement, contempt for others, and rejection of truth, and driven by pride in knowledge, lineage, wealth, or social status. The maqāṣid khāṣṣah of Surah Luqman verse 18 is identified as ḥifẓ al-karāmah al-insāniyyah, or the protection of human dignity, which is actualized through the cultivation of tawāḍu‘ and the establishment of egalitarian social relations. This objective extends beyond individual moral reform by providing a normative foundation for rejecting status-based humiliation and image-driven superiority. Verification through classical and contemporary exegetical perspectives further demonstrates that the verse functions as an ethical framework for realizing relational justice in both conventional and digital social contexts, including responses to social climbing (pansos) and narcissistic self-presentation. By grounding human worth in piety rather than worldly distinctions, this study contributes a Qur’anic ethical framework for fostering humility, mutual respect, human dignity, and harmonious coexistence within diverse societies.